Objective Dialecticity: Features and Values - Aliūkaitė, Daiva (Respectus Philologicus, 2019)
[full article and abstract in Lithuanian; abstract in English]The article focuses on the discourse of perceptual dialectology with the emphasis on the issue of the objective dialecticity. The aim to analyse the question of the objective dialecticity as a dialect parameter is essentially an attempt to identify the linguistic features of the dialect artefact that distinguish this artefact from other observation artefacts from the perspective of an ordinary member of the language community. Thus, the article, based on the data of language attitudes and perception of variants, develops an illustrative discourse, which reveals the features and values of the objective dialecticity from the perspective of an ordinary member of the Lithuanian language community.The research data reveals that the system of the objective dialecticity features of ordinary members of the language community encompasses distinctive, characteristic, and fuzzy dialectal features. Only more characteristic and intense prominent secondary (characteristic) and tertiary (fuzzy) features in the horizontal continuum of the regional language variance determine that ordinary members of the language community (re)construct the dialect artefact on the basis of the latter.
Keywords: perceptual dialectology; objective dialecticity; dialect artefact; Standard Language